IBD for the non-gastroenterologist - Kane, Sunanda (Henry Stewart Talks, 2021)
Clinical epidemiology and characteristics of IBD, Diagnostic testing, Medical treatment of UC and CD, Adverse events with medications, Assessing extraintestinal manifestations of IBD, Complications of disease, Alternative Therapies for IBD, Vaccination advice, Mental health issues, Cancer screening